A Mathematical Model for Weighted Multicriteria Assignment Problem: An Empirical Study - Mercangoz, Burcu Adiguzel (International Journal of Advanced Research in Engineering; Vol 2 No 1 (2016): International Journal of Advanced Research in Engineering, 2016)
Assignment is a key issue for the most planning process. It has always a big importance for the planning process. In most cases assignment is being done with more than one variable, taking in to consideration of both qualitative and quantitative variables. In this study a mathematical model for the weighted multicriteria assignment problem is developed and the results are displayed on a numerical example. The given numerical example is about to assign the faculty to the final exams of the courses. There are some constraints for the faculty according to their program. So they are given a matrix for the exams that they are available to be assigned. This study is unique that there has not been found a study with such this objective and these constraints. The problem examined is an integer programming with weighted objective to the best of my knowledge. A mathematical model is developed for the solution of this assignment problem. The effectiveness of the proposed modelis validated by its application to an empirical example dealing with weighted multiobjectiveassignment problem.